Expression of LINE-1 elements is required for preimplantation development and totipotency - Ru Ma; Nan Xiao; Na Liu (Genes and Diseases)
Transposable elements, long considered genomic intruders, have been found to play significant and intriguing roles during early embryonic development based on the paradigm shift that has undergone in recent years. Long interspersed element-1 (LINE-1) is the predominant class of retrotransposons with autonomous retrotransposition capabilities in mammals and has emerged as a crucial element of preimplantation development. In this review, we elucidate the expression dynamics of key transposable elements throughout preimplantation development and their contribution to the regulation of developmental progression and totipotency. We also explore the critical function of LINE-1 activation and its rich functional reservoir, which is exploited by the host to provide cis-regulatory elements and functional proteins. Particular highlights of the widespread activities in preimplantation development of LINE-1 during multiple epigenetic modifications such as DNA methylation, histone methylation, ubiquitination, and RNA methylation. The silencing complex and RNA exosome also coordinate with LINE-1 across distinct developmental stages. Accordingly, the up-regulated expression of LINE-1 retrotransposons and their protein products plays a key role in various processes, including the opening of chromatin architecture, zygotic genome activation, aging, and age-related disorders. It may reflect an effect on totipotency and pluripotency of mammalian development. Underscoring its pivotal significance, the nuanced regulation of LINE-1 illuminates its indispensable role in orchestrating the precise coordination essential for the regulation of cellular pluripotency and the intricate mechanisms of zygotic genome activation.